Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có: (6x – 39) : 3 = 201
6x – 39 = 201 . 3
6x – 39 = 603
6x = 603 + 39
6x = 642
x = 642 : 6
x = 107
[ ( 6x - 39 ) : 7 ] . 4 = 12
=> ( 6x - 39 ) : 7 = 12 : 4
=> ( 6x - 39 ) : 7 = 3
=> 6x - 39 = 3.7
=> 6x - 39 = 21
=> 6x = 21+39
=> 6x = 60
=> x = 10.
( x : 3 - 4 ) . 5 = 15
=> x : 3 - 4 = 15 : 5
=> x : 3 - 4 = 3
=> x : 3 = 7
=> x = 7.3
=> x = 21
x - [ 42 + (-28) ] = -8
=> x - 14 = -8
=> x = -8 + 14
=> x = 6.
[ (6x - 39): 7] . 4=12
(6x-39) : 7=12:4
(6x -39) :7=3
(6x-39) =3 . 7
6x-39 =21
6x =21 +39
6x=20
x=10
[ ( 6 . x - 39 ) : 7 ] . 4 = 12
[ ( 6 . x - 39 ) : 7 ] = 12 : 4
( 6 . x - 39 ) : 7 = 3
6 . x - 39 = 3 . 7
a) (x : 3 - 4) . 5 = 15
x : 3 - 4 = 15 : 5
x : 3 - 4 = 3
x : 3 = 3 + 4
x : 3 = 7
x = 7 . 3
x = 21.
6 . x - 39 = 21
6 . x = 21 + 39
6 . x = 60
x = 60 : 6
x = 10
Vậy x = 10
9.3x+1 = 81
= 81
[(6x-39):7].4=12 (x:3-4).5=15 9.3x+1=81
(6x-39):7 =12:4=3 x:3-4 =15:5=3 27x+1=81
6x-39 =3.7 =21 x:3 =3+4=7 x+1=81:27=3
6x =21+39=60 x =7.3=21 x =3-1=2
x =60:6 =10
( 6x - 39 ) : 3 = 201
6x - 39 = 603
6x = 642
x = 107
23 + 3x = 56 : 53
23 + 3x = 125
2x = 102
x = 51
(6x - 39):3=201
6x:3 - 39 :3=201
2x - 13 =201
2x=201+13
2x=214
x=214:2
x=107
a) 25 + 3x = 25 - 1
3x = -1
x = -1/3
b) (6x-39):13 = 201
6x-39 = 2613
6x = 2652
x = 442
c) 2x + 35:34 = 510 : 58
2x + 3 = 25
2x = 22
...